2019
DOI: 10.1111/aor.13518
|View full text |Cite
|
Sign up to set email alerts
|

Teburu—Open source 3D printable bioreactor for tissue slices as dynamic three‐dimensional cell culture models

Abstract: Three-dimensional tissue cultures are important models for the study of cell-cell and cell-matrix interactions, as well as, to investigate tissue repair and reconstruction pathways. Therefore, we designed a reproducible and easy to handle printable bioreactor system (Teburu), that is applicable for different approaches of pathway investigation and targeted tissue repair using human tissue slices as a three-dimensional cell culture model. Here, we definitively describe Teburu as a controlled environment to rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…This may be due to numerous in-house developments and optimizations in the field of fluidic MBR as PDMS is comparatively easy to process and to shape. Occasionally, 3D printed systems are also used [2,3]. Another large group of widely used MBRs, the RWV bioreactor type, is usually based on commercially available systems, e.g., from Synthecon.…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to numerous in-house developments and optimizations in the field of fluidic MBR as PDMS is comparatively easy to process and to shape. Occasionally, 3D printed systems are also used [2,3]. Another large group of widely used MBRs, the RWV bioreactor type, is usually based on commercially available systems, e.g., from Synthecon.…”
Section: Resultsmentioning
confidence: 99%
“…As well as an in vivo-like structure, these tissues also provide the ECM. The models cover decellularized tissue slices [208] and also decellularized whole organs [204] with permission of Springer Nature (C) Bioreactor system of Mahmoudifar and Doran consisting of two separate culture chambers containing osteogenic respectively chondrogenic medium (left). Up to three triplicate PGA disk scaffolds can be mounted between the two chambers (right).…”
Section: Decellularized Tissues In Fluidic Micro-bioreactorsmentioning
confidence: 99%
“…As well as an in vivo-like structure, these tissues also provide the ECM. The models cover decellularized tissue slices [208] and also decellularized whole organs [209]. The system of Daneshgar et al [208] consisted of decellularized human liver slices, which they reseeded with human mesenchymal stromal cells, in a printed, so-called Teburu perfusion bioreactor.…”
Section: Decellularized Tissues In Fluidic Micro-bioreactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assal Daneshgar et al of the Humboldt‐Universität zu Berlin, Berlin, Germany reported on their three‐dimensional tissue culture printable bioreactor system (Teburu) that is applicable for different approaches of pathway investigation and targeted tissue repair using human tissue slices as a three‐dimensional cell culture model. They discussed reseeding a 500‐µm thick decellularized human liver slice using human mesenchymal stroma cells.…”
Section: Tissue Engineeringmentioning
confidence: 99%